N-Alkylated dinitrones from isosorbide as cross-linkers for unsaturated bio-based polyesters - Goerz, Oliver; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2014)
Isosorbide was esterified with acryloyl chloride and crotonic acid yielding isosorbide diacrylate (9a) and isosorbide dicrotonate (9b), which were reacted with benzaldehyde oxime in the presence of zinc(II) iodide and boron triflouride etherate as catalysts to obtain N-alkylated dinitrones 10a/b. Poly(isosorbide itaconite -co- succinate) 13 as a bio-based unsaturated polyester was cross-linked by a 1,3-dipolar cycloaddition with the received dinitrones 10a/b. The 1,3-dipolar cycloaddition led to a strong change of the mechanical properties which were investigated by rheological measurements. Nitrones derived from methyl acrylate (3a) and methyl crotonate (3b) were used as model systems and reacted with dimethyl itaconate to further characterize the 1,3-dipolaric cycloaddition.
Keywords: bio-based polyesters; cross-linkers; dinitrones; 1,3-dipolar cycloaddition; isosorbide